2017
DOI: 10.1111/rda.12998
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessment of pulmonary fluid clearance and lung aeration in newborn calves delivered by elective Caesarean section

Abstract: The aim of this study was to develop a radiographic standard for the assessment of pulmonary fluid clearance and lung aeration in newborn calves. Caesarean-delivered mature calves (n = 9) underwent lung assessment by thoracic radiography as well as arterial and venous blood gas analysis within the first 30 min, 1, 2, 3, 6, 12 and 24 hr after birth. The results indicated that newborn calves delivered by elective Caesarean section suffered from a physiological combined respiratory and metabolic acidosis with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, the time required for complete pulmonary ventilation and the order in which different lung regions become ventilated remain unclear. Ventilation of all lung regions in neonatal calves was seen within 12 h using ultrasonography [ 12 ], 24 h using radiography [ 13 ], and 14 days after birth using computed tomography [ 14 ]. Pulmonary ventilation was reported to be progressive in all those studies, but whether certain lung regions become ventilated earlier than others, which remain nonventilated (silent spaces) or poorly ventilated, or whether all regions become ventilated more or less simultaneously was not determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the time required for complete pulmonary ventilation and the order in which different lung regions become ventilated remain unclear. Ventilation of all lung regions in neonatal calves was seen within 12 h using ultrasonography [ 12 ], 24 h using radiography [ 13 ], and 14 days after birth using computed tomography [ 14 ]. Pulmonary ventilation was reported to be progressive in all those studies, but whether certain lung regions become ventilated earlier than others, which remain nonventilated (silent spaces) or poorly ventilated, or whether all regions become ventilated more or less simultaneously was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Areas with persistent incomplete ventilation appeared as radiodensities in the perihilar lung regions. In neonatal calves born via Caesarean section, monitoring of pulmonary ventilation via radiography showed that ventilation was not complete until 24 h postnatum, and fluid resorption occurred more quickly in the ventral rather than the dorsal areas of the lungs [ 13 ]. Computed tomography (CT) of the lungs of sedated calves revealed that the greatest increase in pulmonary ventilation occurred in the first 6 h postnatum [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the calves had pulmonary opacity, frequently restricted to one of the hemithorax (focal). Abdelmegeid et al [ 9 ] showed that complete pulmonary clearance in elective Caesarean-delivered neonatal calves is established only within 24 hours of birth, with thoracic radiographic images compatible with clear lung fields, lung expansion, air content of the lung and absence of lung opacification. On the other hand, both neonatal foals and lambs exhibit clear lung fields by thoracic images up to 6 hours of life, by the time pulmonary pathologic disorders can be diagnosed [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal calves, lung compliance increases and lung resistance decreases over time, mainly during the first 6 hours after birth [ 8 ]. Moreover, complete pulmonary clearance is only achieved within 24 hours of birth [ 9 ]. Therefore, radiographic assessment for the purpose of diagnosing pulmonary neonatal disorders should be considered concomitantly with clinical signs and evaluation of blood acid-base imbalance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were randomly allocated into two groups: the control group (receiving no betaine, n=15) and the betaine group (supplied with 80 g betaine/day for 4w, n=15). In this study, we selected this high dosage of betaine to explore its potential impact on the observed parameters, considering previous research findings [25,26]. In a powdered form, the betaine supplement was well mixed with 50 ml of cane molasses to ensure thorough integration of all betaine particles.…”
Section: Animals Diets and Betaine Supplementmentioning
confidence: 99%